2011
DOI: 10.5562/cca1784
|View full text |Cite
|
Sign up to set email alerts
|

PEDOT Modified Carbon Paste Microelectrodes for Scanning Electrochemical Microscopy

Abstract: Abstract. Only one measuring tip was used in three different modes of operation of the Scanning Electrochemical Microscope (feed-back mode, generation-collection mode, potentiometry) to collect chemical information about copper targets. The tip was formed from 5 and 25 μm diameter conventional platinum microdisk electrode by etching a cavity, then electrochemically depositing poly(3,4-ethylenedioxythiophene) (PEDOT) layer doped with hexacyanoferrate and finally filling with modified carbon paste based Cu 2+ se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…A number of reviews and books describe the preparation, characterization, and use of carbon paste electrodes for various purposes. In spite of its wide variety of applications as the electrode material or as sensor substrate, reports on carbon paste UMEs are limited. The first report of a carbon paste microelectrode was by Kissinger et al Later, Martin and co-workers reported the preparation of carbon paste microelectrode arrays. , In some recent reports carbon paste UMEs were used as sensing electrodes. Carbon paste UMEs modified with a biological sensing molecule should be useful in imaging biological substrates when used as the tip in an SECM. To our knowledge only two reports deal with the carbon paste UMEs with ≤10 μm diameters. , No reports show well-defined steady-state cyclic voltammograms with carbon paste UMEs or its application in SECM measurements, especially with the formation of micrometer to nanometer gaps using the SECM approach.…”
mentioning
confidence: 99%
See 3 more Smart Citations
“…A number of reviews and books describe the preparation, characterization, and use of carbon paste electrodes for various purposes. In spite of its wide variety of applications as the electrode material or as sensor substrate, reports on carbon paste UMEs are limited. The first report of a carbon paste microelectrode was by Kissinger et al Later, Martin and co-workers reported the preparation of carbon paste microelectrode arrays. , In some recent reports carbon paste UMEs were used as sensing electrodes. Carbon paste UMEs modified with a biological sensing molecule should be useful in imaging biological substrates when used as the tip in an SECM. To our knowledge only two reports deal with the carbon paste UMEs with ≤10 μm diameters. , No reports show well-defined steady-state cyclic voltammograms with carbon paste UMEs or its application in SECM measurements, especially with the formation of micrometer to nanometer gaps using the SECM approach.…”
mentioning
confidence: 99%
“…The first report of a carbon paste microelectrode was by Kissinger et al Later, Martin and co-workers reported the preparation of carbon paste microelectrode arrays. , In some recent reports carbon paste UMEs were used as sensing electrodes. Carbon paste UMEs modified with a biological sensing molecule should be useful in imaging biological substrates when used as the tip in an SECM. To our knowledge only two reports deal with the carbon paste UMEs with ≤10 μm diameters. , No reports show well-defined steady-state cyclic voltammograms with carbon paste UMEs or its application in SECM measurements, especially with the formation of micrometer to nanometer gaps using the SECM approach. There have been reports on electrodes based on ultramicro-/nanocavity formation in glass. The cavities were filled with electrocatalyst materials, and catalyst UMEs were prepared; these were used for the evaluation of the catalytic activity and studying active sites in the catalyst materials. , Nanopore electrodes in glass have also been described for investigation of molecular transport through the pores. In a recent report, carbon was deposited by burning butane inside a glass nanopore to produce a carbon nanoelectrode for SECM applications …”
mentioning
confidence: 99%
See 2 more Smart Citations